2022
DOI: 10.3389/feduc.2022.944567
|View full text |Cite
|
Sign up to set email alerts
|

Mapping SS1-3 chemistry teachers’ interest, self-efficacy, and literacy in teaching for creativity using simulation

Abstract: The purpose of this article was to analyze chemistry teachers’ interest, literacy, self-efficacy, teamwork, and creativity in the use of simulation teaching of concepts in chemistry to enhance students’ creativity skills. A descriptive and exploratory quantitative design was used in the study. The study used 150 serving chemistry teachers from the Calabar education zone public education system. A 29-item questionnaire was employed to gather data from respondents. Independent t-test, regression, and a 2-way ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The years 2020 and 2021 showed no article publication. The following year, 2022, there were 11 articles (Steinwachs & Martens, 2022;Alghamdi et al, 2022;Jimenez et al, 2022;Cooper et al, 2022;Luft et al, 2022;Chan & Erduran, 2022;Wallace et al, 2022;Abdulbakioglu et al, 2022;Zoupidis et al, 2022;Buma & Sibanda, 2022;Nja et al, 2022). The year 2023 showed the highest number of articles, with 14 articles (Schofield et al, 2023;Busch et al, 2023;Lilly et al, 2023;Rachmatullah et al, 2023;Peters-Burton et al, 2023 Therefore, the year of publication in 2023 shows the highest percentage, 53.86 percent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The years 2020 and 2021 showed no article publication. The following year, 2022, there were 11 articles (Steinwachs & Martens, 2022;Alghamdi et al, 2022;Jimenez et al, 2022;Cooper et al, 2022;Luft et al, 2022;Chan & Erduran, 2022;Wallace et al, 2022;Abdulbakioglu et al, 2022;Zoupidis et al, 2022;Buma & Sibanda, 2022;Nja et al, 2022). The year 2023 showed the highest number of articles, with 14 articles (Schofield et al, 2023;Busch et al, 2023;Lilly et al, 2023;Rachmatullah et al, 2023;Peters-Burton et al, 2023 Therefore, the year of publication in 2023 shows the highest percentage, 53.86 percent.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the research design graph shown in Figure 3, mixed methods were most widely used in the articles, namely as many as 14 articles (Alghamdi et al, 2022;Jimenez et al, 2022;Busch et al, 2023;Lilly et al, 2023;Luft et al, 2022;Peters-Burton et al, 2023;Wulff et al, 2023;Fridberg et al, 2023;Davis & Palincsar, 2023;Nilsson & Lund, 2023;Mouza et al, 2023;Abdulbakioglu et al, 2022;Buma & Sibanda 2022;Becerra et al, 2023). Apart from that, quantitative descriptive also has eight articles (Poce et al, 2019;Schofield et al, 2023;Schofield et al, 2023;Rachmatullah et al, 2023;Zoupidis et al, 2022;Vasconcelos & Paz, 2023;Nja et al, 2022;& Alghamdi 2023). Five articles have been identified for the qualitative study design (Steinwachs & Martens, 2022;Cooper et al, 2022;Cooper et al, 2022;Wallace et al, 2022& Mathis et al, 2023.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If a student believed she/he can pass an examination that student can pass that particular examination [ [59] , [60] , [61] ]. [ 62 ] stated that self-efficacy has been discovered as a potent force that directs students' performance. A study by Refs.…”
Section: Discussionmentioning
confidence: 99%
“…This showed that students have not been doing well in chemistry examination in WAEC as there was no year that students score up to 70% in the years under review. The method of imparting knowledge to a learner is one of the most cited areas of science education that has been facing several challenges which according to Nja, Orim, Cornelius-Ukpepi, and Ndifon (2022b) most researchers internationally and locally are seeking for solutions to problems or to improve on existing situations. Based on this fact, Okebukola (2002) identified three fundamentally different approaches to learning science: behaviorism, cognitivism, and constructivism.…”
Section: Introductionmentioning
confidence: 99%